The Principle of Global Axiology: ’’The Shepherd’s Rod’’ for the Whole Human Name - Botezatu, Liuba (Advances in Social Sciences Research Journal, 2022)
We want peace and not war is the calling of the whole world. It is our daily calling. How do we pedagogues of all levels respond to the call of immortality? This is the Ion Druță’s calling to which we align by thinking and acting in the context of our being, directly of the being of the whole world, the Principle of Global Axiology - "The shepherd’s rod" of the whole human race. It is appropriate to emphasize the achievements of the creation of the entire human race in cultural, economic and social diversity. This is the case of our everyday occupation in which, in the format of set theory, the accents of complementary meaning the theory of multiple graces / TGM (L. Botezatu) - the theory of multiple intelligences / TIM (H. Gardner) guarantees its philosophical-centric positioning. It is the fact that the Paideia art reaches the peaks of the first signs of the markers in accessing "to be here". It is the day-to-day operation of "being beyond", vocally engaged in the work of responsibility for value resignation. Know how to choose the most efficient epistemic configurations; to order them and subject them to the laws of the mechanics of action by connecting the PAG/ Principle of Global Axiology from the TMSC/ Theory and Special Methodologu of Creativity (vis-à-vis the specific concerns of the embraced field) to the TMGC/ Theory and General Methodoogy of Creativity means to diligently replace yourself on the scale of meritological practices; return to essence - ascension through Spirituality into the Great Spirituality.